Chapter Il contributo di Paolo Federighi sulle politiche transnazionali nello sviluppo dell'Educazione degli Adulti. Il modello delle learning city e learning region - Piazza, Roberta (Studies on Adult Learning and Education, 2022)
The essay is a tribute to Paolo Federighi for his role as a magister and researcher in the area of learning and education of adults. Through a brief excursus of more than twenty years, from my first steps as a researcher to my recent experience as a member of the Scientific Committee of Lucca Learning city - the attempt is to highlight the level of influence that his reflections had on my interest in education policies in adulthood education and on embracing the learning city model.